خصائص الكلمة ودورها في البنيَّة الحجاجيَّة في الإعلام المرئي = The characteristics of the word and its role in the argumentative structure in the visual media - Aboudaher, Moustafa Elsayed Mohmed; Ali, Asem Shehadeh Saleh (Ministry of Higher Education and Scientific Research -Algeria, 2020)
تنطلق فرضيَّة هذا البحث من أن الخطاب الحجاجيّ هو خطاب تواصليّ وعمل لغويّ حجاجيّ تفاعليّ؛ ومن ثم فللكلمة في التراث العربيّ دور حجاجي،ولا نتقائها حركة حجاحية تاثيرية في المتلقي، فبدأ البحث بضبط الإطار المفاهيهيم للكلمة في التراث العربي وعند المعاصرين الغربيين والعرب، في محاولة للبحث عن الجذور التاريخية للكلمة في التراث العربيّ ومدى انطباقها مع مفهوم الكلمة اليوم، فضلاً عن بيان أثرها في الخطاب الحجاجي لا سيما في الإعلام المرئيّ، وقد اعتمد الباحث المنهج الوصفيّ والمنهج التحليليّ بهدف تحليل النماذج المختارة من برنامج "الاتجاه المعاكس" بقناة ؛ الجزيرة، تحليلاً تداوليّاً حجاجيّاً؛ لبيان تأثير الحركة الحجاجيَّة للكلمة، فضلاً عن بيان الحمولة الحجاجيَّة وطاقتها التأثيريَّة، وبيان مدى حجاجيَّة الكلمة المفردة عبر الحمولات الثلاث: الدلاليَّة والسياقيَّة والإيقاعيَّة. فضلًا عن بيان أن المعنى المعجميّ وحده ليس هو سبب اختيار اللفظ بل يُعد السياقان الداخليّ والخارجيّ بتنوع عناصرهما هما الدافع الحجاجيّ للعدول عن لفظ واختيار آخر.. ********************************************************************************* The hypothesis of study is assumption from the truth that the argumentative discourse is a communicative discourse and an interactive argumentative linguistic work. Hence, the complement has an argumentative role on the recipient. The study setting the conceptual framework for wisdom in Arab heritage and among Western and Arab contemporaries to search for the historical roots of the word in the Arab heritage and the extent of its applicability with the concept of the words today, as well as showing its impact on the speech of argumentative, especially in the visual media. The study adopted a descriptive and an analytical approach; In order to analyse the selected models from the Al- Jazeera debate program “The Opposite Direction”. The study analyses the impact of the argumentative movement of the word. The study reached to the conclusions that the word has an argumentative load and influence energy; the single word Manifested through three loads: semantic, contextual, and rhythmic. Moreover, The lexical meaning alone is the reason for choosing the word. Rather, the internal and external contexts with the diversity of their elements are the augmentative’s motivation to refrain from the word and another choice